A cross-sectional analysis on the patterns and prevalence of anxiety, stress, and depression in patients at diagnosis with cancers of the oral cavity: A single institutional study - Roy, Sharmistha; Debottam Barman,; Nitu Mallik,; Snigdha Hazra,; Asit Ranjan Deb,; Samik Pramanik, (Asian Journal of Medical Sciences, 2024)
Background: It is a truth universally acknowledged that the diagnosis of cancer is a huge stress for both individuals and families. While many psychosocial variables have been shown to influence the mental well-being, these factors are so complicated and interlinked with each other, that their integrated effect on oral cancer patients, who constitute a large morbid group of patients, is yet to be recognized. Aims and Objectives: The present research work aims to find more about the prevalence of stress, anxiety, and depression among patients with cancers of the oral cavity and work out on some key potentially predictive factors associated with anxiety and depressive symptoms. Materials and Methods: A cross-sectional observational study was carried out for patients of oral cancer, attending the radiation oncology out-patient department (OPD) at Medical college, Kolkata, between April 2022 and March 2023, a 1-year period. A total of 89 patients with oral cancer were interviewed with questionnaires on demographic variables, depression anxiety stress scale 21, and National Comprehensive Cancer Network Distress Thermometer. Chi-square tests and Spearman Correlation tests were conducted where appropriate to explore relationships between different variables. Results: The prevalence of stress symptoms, anxiety symptoms, and depressive symptoms was 44% (39/89), 60% (53/89), and 84% (75/89), respectively, among the patients interviewed. Addiction history of the patients was an important association found in this study. Conclusion: The prevalence of stress and depressive symptoms was high among the oral cancer patients attending the Radiation Oncology OPD at our institution as well as levels of anxiety. Certain social variables such as relationship with spouse, children, and other family members had a profound effect on the mental well-being of the patients. Furthermore, certain factors such as addiction to tobacco and its different forms reduced the coping up capability of the patients.